The effect of ply folds as manufacturing defect on the fatigue life of CFRP materials (Fracture and Structural Integrity, 2016)
Manufacturing defects are inherent to any manufacturing process. However, in composite materials they might be unavoidable, e.g. ply waviness or even folds of plies are present in complex shaped parts during high pressure resin transfer molding of carbon fiber reinforced polymers. In this work, the effect of the ply folds on the fatigue life of the composite material is investigated. Folds along fiber direction (as they commonly appear during manufacturing) were artificially introduced in unidirectional non crimp fabric plies. The target of this study is the prediction of damage initiation due to this particular type of manufacturing defect. The folds locally increase the fiber volume fraction and also introduce resin rich areas. Fatigue tests in fiber direction and transverse to fiber direction are performed at different load ratios under constant amplitude loading. The influence of the defect geometry on damage initiation and progression is investigated at different scales by non-destructive methods before testing, continuous strain measurement and monitoring the damage progression during testing and fractography analysis after final failure. Most of the time, the first damage was observed at the location of the introduced fold for all considered load cases. However, it was also found, that the folds lead to no significant reduction in fatigue life.
Keywords: Manufacturing defects; CFRP; Fatigue damage; Fold